USING OF TEACHING INTERACTIVE METHODS AT UKRAINIAN AS A FOREIGN LANGUAGE LESSONS: ASPECT OF CREATING FUTURE DOCTORS’ COMMUNICATIVE COMPETENCE - Родчин, З. Я. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article considers the process of creating future doctors’ communicative competence. Besides, it introduces using teaching interactive methods at Ukrainian as a foreign language lessons. The necessity of using communicative approach as well as paying attention to abilities (by Bloom) are shown.